1996
DOI: 10.1074/jbc.271.34.20942
|View full text |Cite
|
Sign up to set email alerts
|

The e Subunit Gene of Murine F1F0-ATP Synthase

Abstract: Genomic sequences encoding murine Lfm1, whose predicted protein sequence is 96% and 98% similar to bovine and rat F 1 F 0 -ATP synthase e subunits (respectively), have been amplified from BALB/cByJ DNA, cloned, and sequenced. The 1.1-kilobase gene has 3 introns and 4 exons, and its coding sequence differs by two nucleotides compared to the previously published BALB/cHnn Lfm1 cDNA sequence. A PstI restriction site polymorphism in intron 2 between C57BL/6J and Mus spretus was used to map this gene to Chromosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Genes involved in the glucose-induced insulin secretion cascade of pancreatic beta-cells are located in the region, such as ATP5I (ATP synthase, H + transporting, mitochondrial F 0 complex, subunit E) [42, 43], CPLX1 (complexin 1) [44, 45], GAK (cyclin G associated kinase) in association with CDK5 (cyclin-dependent protein kinases 5) [4650], and CRIPAK (cysteine-rich PAK1 inhibitor), which is a negative regulator of PAK1 (p21 protein (Cdc42/Rac-) activated kinase 1) [51, 52]. …”
Section: Discussionmentioning
confidence: 99%
“…Genes involved in the glucose-induced insulin secretion cascade of pancreatic beta-cells are located in the region, such as ATP5I (ATP synthase, H + transporting, mitochondrial F 0 complex, subunit E) [42, 43], CPLX1 (complexin 1) [44, 45], GAK (cyclin G associated kinase) in association with CDK5 (cyclin-dependent protein kinases 5) [4650], and CRIPAK (cysteine-rich PAK1 inhibitor), which is a negative regulator of PAK1 (p21 protein (Cdc42/Rac-) activated kinase 1) [51, 52]. …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found ATP5ME and NDUFAF2 were differentially expressed. ATP5ME encodes the e subunit of Fo complex that constitutes the membrane-spanning component of adenosine-triphosphate synthase (42), and the encoding product of NDUFAF2 is the one of the components of complex I in the electron transport chain (43). These results are accordant to impaired complex I, II, and IV in the oxidative phosphorylation system (44,45) and reduced activity of complex in the mitochondrial electron transport chain (46,47) observed by other researchers in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 76%
“…It is important to emphasize that Western blots demonstrated that RBF-specific antibodies do not cross-react to mitochondrial antigens (unpublished observation). The mitochondrial ATP synthase chain is a distinct polypeptide that is a nonenzymatic component of the multiprotein complex located in the mitochondrial membrane that synthesizes ATP (66). This identity supports that RBF protein would form protein-protein interactions, even though the two proteins have very distinct morphological functions.…”
Section: Discussionmentioning
confidence: 81%